Model Komunikasi Penyuluh Agama Islam Dalam Memperkokoh Kualitas Pengetahuan Pemuda yang Majemuk Melalui Pendekatan Humanis Di Kecamatan Besitang Kabupaten Langkat - M. Idris; Wahyu Ziaulhaq (Yayasan Literasi Sains Indonesia, 2022)
This article discusses the communication model of Islamic religious educators in strengthening the quality of diverse youth knowledge in Besitang District, Langkat Regency. This study aims to determine the level of knowledge of young people who are diverse and try to make young people understand the importance of maintaining pluralism. The article method used is qualitative. The approach used is descriptive analysis approach supported by anthropological and sociological approaches. The subjects of this article are Islamic religious educators and youth. Collecting data using observation, unstructured interviews, and decommentation. The results of the research that have been found indicate that the educational quality of youth pluralism in Besitang Subdistrict, Langkat Regency, continues to experience a significant increase in terms of the quality of human resources, besides that, in terms of educational facilities and infrastructure, it continues to receive serious attention from the local government. The communication model carried out by Islamic religious educators in strengthening the quality of youth's diverse knowledge is to prioritize the character of time discipline, always maintain an attitude of tolerance, and avoid horizontal conflicts, get religious education on an ongoing basis, provide motivation and guidance and contribute to the Besitang sub-district government, establish harmonious cooperation with Muslim organizations in order to build a safe and comfortable country.